2012
DOI: 10.3109/10428194.2012.662644
|View full text |Cite
|
Sign up to set email alerts
|

Activation of human leukemic mast cell line LAD2 is modulated by dehydroleucodine and xanthatin

Abstract: The aim of the present study was to determine whether dehydroleucodine, xanthatin and 3-benzyloxymethyl-5H-furan-2-one inhibit the activation of human leukemic LAD2 mast cells induced by compound 48/80 or the calcium ionophore A23187. LAD2 cells were preincubated in the presence of test drugs and then challenged with the secretagogues. This study provides the first evidence in favor of the view that dehydroleucodine and xanthatin inhibit the degranulation of LAD2 cells, thus acting as human mast cell stabilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Previous studies showed that xanthatin had an antitumour effect in several tumour cells, including A549 nonsmall cell lung cancer cells, H1299 nonsmall cell lung cancer cells, B16‐F10 murine melanoma cells, human breast cancer MDA‐MB‐231 cells, HL‐60 cells, the human leukemic mast cell line LAD2, and Chinese hamster ovary cells (Li et al, ; Sanchez‐Lamar et al, ; Takeda, Nishimura, et al, ; Takeda, Noguchi, et al, ; Tao et al, ; Tao et al, ; Tao et al, ; Vera et al, ; Yu et al, ; L. Zhang, Ruan, et al, ). Here, we found that xanthatin significantly inhibited tumour growth in both nude mouse xenograft glioma and rat orthotopic implanted glioma in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that xanthatin had an antitumour effect in several tumour cells, including A549 nonsmall cell lung cancer cells, H1299 nonsmall cell lung cancer cells, B16‐F10 murine melanoma cells, human breast cancer MDA‐MB‐231 cells, HL‐60 cells, the human leukemic mast cell line LAD2, and Chinese hamster ovary cells (Li et al, ; Sanchez‐Lamar et al, ; Takeda, Nishimura, et al, ; Takeda, Noguchi, et al, ; Tao et al, ; Tao et al, ; Tao et al, ; Vera et al, ; Yu et al, ; L. Zhang, Ruan, et al, ). Here, we found that xanthatin significantly inhibited tumour growth in both nude mouse xenograft glioma and rat orthotopic implanted glioma in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Xanthatin, one of the major active compounds of X. strumarium L., has been reported to inhibit the proliferation of tumour cells, such as A549 nonsmall cell lung cancer cells, H1299 non-small cell lung cancer cells, B16-F10 murine melanoma cells, human breast cancer MDA-MB-231 cells, HL-60 cells, the human leukaemic mast cell line LAD2, and Chinese hamster ovary cells (Li et al, 2013;Sanchez-Lamar et al, 2016;Takeda, Noguchi, et al, 2013;Tao et al, 2017;Tao et al, 2013;Tao et al, 2016;Vera et al, 2012;Yu et al, 2015;L. Zhang, Ruan, et al, 2012).…”
mentioning
confidence: 99%
“…It was reported that dehydroleucodine inhibited the degranulation of human leukemic LAD2 mast cells, thus acting as mast cell stabilizers (Vera et al 2012). Interestingly, it was reported that dehydroleucodine-treated cervical cancer HeLa cells became apoptotic, where the greater accumulation of DNA lesions that triggered the activation of ATM were consequently leading to transient G2/M arrest and permanent G1 arrest of HeLa cells (Costantino et al 2013).…”
Section: Artemisia Douglasianamentioning
confidence: 99%
“…Mast cells are considered divergent in various tissue settings, 1,11 are difficult to obtain at scale for assay purposes from such tissues, and are rare in blood. A few mast cell-like cell lines have been reported in the literature, including HMC-1 cells 12,13 and LAD2 cells, 14,15 although culture of these cell lines remains challenging. We chose to use an approach precedented in the literature, using human primary cord blood-derived mononuclear cells, 7,8,[16][17][18] culturing and differentiating the cells to a mast cell phenotype over many weeks, before screening compounds for antagonism of both tryptase release as a marker of degranulation and PGD 2 synthesis as the major arachidonic acid-derived mediator.…”
Section: +mentioning
confidence: 99%